PUBLIC HEALTH, INFECTIOUS DISEASES AND MEAT PACKING INDUSTRY WORKERS: AN INTEGRATIVE REVIEW - Ruiz, Roberto Carlos; Silva, Allan Rodrigo de Campos [UNESP]; Marra, Gabriela Chaves; Menegon, Lizandra da Silva; Mattos, Rita de Cassia Oliveira da Costa; Diesel, Lilian Elizabeth; Franz, Helena Cristina Ferreira; Okamoto, Kenichi; Menegon, Fabricio Augusto (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2025)
The meat industry is responsible for about 5.7% of Brazil's GDP, employing 639,000 workers directly, who are exposed to diverse labor risks during their work day. This research objective is to understand the set of infectious diseases that can affect these workers, based on exposure to biological risk in their work environment, creating a single list of microorganisms that cause such diseases. Method: We performed an integrative bibliographic review with pre-defined descriptors, from a search in 11 databases (COCHRANE Library; EMBASE; LILACS; PubMed/MEDLINE; SciELO; Web of Science; Scopus; ProQuest Dissertations & Theses Global- PQDT Global ; Banco de Theses da CAPES; Biblioteca Digital Brasileira de Disserta & ccedil;& otilde;es- BDTD), with the initial selection of 714 scientific publications for analysis of titles and abstracts and, among these, 111 articles for detailed analysis. Results: with the integrated analysis of the selected publications, it was possible to compile a list of most of the microorganisms that can infect workers in the meat industry, during the exercise of their work. We suggest that creating this list is the initial step towards advancing in the better understanding of this topic, with positive impacts on health and safety at work, as well as for public health in general. Conclusions: we suggest some proposals for applying the knowledge systematized in this study: a) qualify the health surveillance system for workers in meat processing plants; b) establish a mandatory vaccination program for workers in this sector; c) creation of a new annex in NR 36, where Brazilian government publicizes the set of biological agents found in these establishments, as in Annex II of NR 32; d) changes related to the classification of unhealthiness in Annex 14 (biological risks) of NR 15; e) changes in the framework for counting special activity time (special retirement) for this group of workers.
Keywords: Public Health; Worker's Health; Infectious diseases; Work-related Diseases; Unhealthiness; Meat Processing Plants